Health Care Provider Accommodations for Patients With Communication Disorders. Issue 4 (October 2017) - Burns, Michael I.; Baylor, Carolyn; Dudgeon, Brian J.; Starks, Helene; Yorkston, Kathryn
Abstract : Health care providers can experience increased difficulty communicating with adult patients during medical interactions when the patients have communication disorders. Meeting the communication needs of these patients can also create unique challenges for providers. The authors explore Communication Accommodation Theory (H.Giles, 1979 ) as a guide for helping providers learn to adapt, or accommodate, their communication style at the appropriate level (neither too much nor too little) when their patients have communication disorders. Using principles of Communication Accommodation Theory, this article navigates case examples of medical interactions involving 2 hypothetical patients, 1 with aphasia and 1 with dysarthria. We use these two patients to illustrate some appropriate accommodations for patients with aphasia or dysarthria. Suggested accommodations stem from the FRAME mnemonic for communicating with patients with communication disorders and are organized using SEGUE, a framework outlining specific steps in a typical medical interaction. This article may also serve as a resource for speech–language pathologists providing in-services to their health care colleagues on this topic and to support interprofessional practices.